Elements explaining learning clinical reasoning using simulation games - Koivisto J-M.; Haavisto E.; Niemi H.; Katajisto J.; Multisilta J. (Serious Games Society, 2022)
This article presents the findings on which elements in a game-based simulation affect learning clinical reasoning in nursing education. By using engaging gaming elements in virtual simulations and integrating the clinical reasoning process into game mechanics, games can enhance learning clinical reasoning and offer meaningful learning experiences. The study was designed to explore how nursing students experience gaming and learning when playing a simulation game, as well as which gaming elements explain learning clinical reasoning. The data was collected by questionnaire from nursing students (N = 166) in autumn 2014 over thirteen gaming sessions. The findings showed that usability, application of nursing knowledge, and exploration have the most impact on learning clinical reasoning when playing simulation games. Findings also revealed that authentic patient-related experiences, feedback, and reflection have an indirect effect on learning clinical reasoning. Based on these results, more efficient simulation games to improve clinical reasoning may be developed.